Seasonal Variation of Epipelic Algal Flora in Günyüzü Pond (Eskisehir/Turkey) - Pabuccu, Koksal; Gulecek, Rabia; Nadir Solak, Cuneyt (Asian Journal of Chemistry, 2010)
In this study, the algal composition of epipelic algae in Günyüzü irrigation pond was investigated between August 2007 and July 2008 and totally 70 taxa were found belong to bacillariophyta (55), chlorophyta (9) and cyanophyta (6). As a result, Achnanthes linearis (W. Smith) Grunow, Amphora ovalis (Kützing) Kützing, Caloneis silicula (Ehrenberg) Cleve, Cyclotella kützingiana Thwaites, Navicula cryptocehala Kützing, Nitzschia dissipata (Kützing) Grunow, N. palea (Kützing) W. Smith and Microcyctis aeruginosa (Kützing) Kützing were most common and dominant in the pond. The physico-chemical features showed that this pond contains soft and clear water.